It’s a residence; it’s a hotel : it is resitel! - Das, Prashant; Gupta, Ashish (London : Indian Institute of Management, Ahmedabad, 2024)
Midway through construction, a hotel developer realises that construction costs had shot up too much to be feasible for equity capital. They reposition the asset as a condominium hotel (naming it "ResiTel") wherein each suite will be sold as a condominium unit to retail buyers. This called for setting up two separate entities: One (PropCo) for asset management and the other (LeaseCo) for operating the hotel. Unit owners would earn a regular share of hotel income. The lenders protect additional sale-risk by more conservative loan terms. The developer must analyse the feasibility of the repositioned asset.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Stocks -- Case studies